2017
DOI: 10.18697/ajfand.79.15855
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics and acceptability of low cost weaning blends by Zambian mothers

Abstract: Stunting, and to a lesser extent wasting and undernutrition, of children under five years constitutes a serious health problem in Zambia. Although non-nutritional causes such as infection and poverty importantly exacerbate these conditions, improvements in the diets of children is vital for better health. The age interval beginning at about six months is an especially vulnerable time for children, when they are being weaned from breast milk to conventionally used cultural foods. The current study reports asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Bambara groundnut protein hydrolysate and peptide fractions could potentially serve as ingredients in the formulation of functional foods and nutraceuticals (Arise et al, 2017). As a cereal-legume-based (maize and Bambara groundnut) complementary food, Bambara groundnut serves as complementary feeding especially those formulated with locally available ingredients (Uvere et al, 2010;Attaugwu et al, 2016;Nwadi et al, 2020;Hayes et al, 2017). In addition, Bambara groundnut represent a good source of insoluble dietary fibre (Diedericks and Jideani, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bambara groundnut protein hydrolysate and peptide fractions could potentially serve as ingredients in the formulation of functional foods and nutraceuticals (Arise et al, 2017). As a cereal-legume-based (maize and Bambara groundnut) complementary food, Bambara groundnut serves as complementary feeding especially those formulated with locally available ingredients (Uvere et al, 2010;Attaugwu et al, 2016;Nwadi et al, 2020;Hayes et al, 2017). In addition, Bambara groundnut represent a good source of insoluble dietary fibre (Diedericks and Jideani, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bambara groundnut has been reportedly used in complementary feeding. Uvere, Onyekwere, and Ngoddy (2010) and Attaugwu, Nwadi, and Uvere (2016) produced cereal‐legume‐based (maize and bambara groundnut) complementary food, whereas Hayes, Zulu, Mulenga, and Kaputo (2017) compared the acceptability of complementary foods formulated with locally available ingredients. It was reported that mothers/guardians of children 5 to 30 months old evaluated the product and the product with bambara groundnut as the chief ingredient was highly acceptable.…”
Section: Introductionmentioning
confidence: 99%